The electrokinetic stabilization (EKS) impact on soft soil (peat) stability towards its physical, mechanical, and dynamic properties at Johor state, Peninsular Malaysia - Abdul Wahab, Abdul Wahab; Embong, Zaidi; Ahmad Tajudin, Saiful Azhar; Uz Zaman, Qamar; Ullah, Hidyat (Elsevier, 2021)
Peat is considered one of the most problematic soils in the construction industry due to its poor physical, mechanical, and dynamic properties. It exists in the coastal part of peninsular Malaysia, and covers almost 8% of the country's land. Therefore, building or road foundations on peat in the coastal region are deemed a serious threat to construction engineers. Thus, it's essential to strengthening its weak properties. This study aims to improve the physical, mechanical, and dynamic peat properties, including shear strength, maximum dry density, moisture content, liquid limit, and shear wave velocity. The soil samples were collected from different locations in Parit Botak area, Batu Pahat District, Johor state, Peninsular Malaysia. The electrokinetic stabilization (EKS) method was applied with an operated electric gradient of 150 V through an aluminum electrode on anode and cathode for 6 hours. As a result, the change in moisture content, liquid limit, density, and shear wave velocity has indicated that post-treatment stability has been improved. It is, therefore, concluded that the EKS technique is effective and capable of strengthening the properties of soft soil.